Analisis Bibliometrik terkait Penelitian Aliran Sesat Berdasarkan Dimensions - Aria Rahman (UIN Sunan Gunung Djati Bandung, 2023)
One of the societal phenomena that affect Indonesian religion is the existence of heretical cults. This study aims to discuss the mapping related to the analytical view of the cults in Islam. This study uses bibliometric analysis to explain quantitative data on studies of heretical sects in Islam. Data were collected from searches in the Dimensions database with the search keyword `Hereticism in Islam` related to two categories, namely: category keywords and articles with data restrictions 2013-2022. In the research category, heretical sects in Islam are dominantly researched in the field of Philosophy and the Study of Religions. The development trend of research on Deviant Sects in Islam increased from 2013 to 2017 with the highest number of studies occurring in 2017 which then decreased from 2017 to 2022. The dominant researchers regarding the number of publications were 2 researchers, namely Ahmad Fauzi Abdul Hamid and Moh Rosyid, each of whom 8 publications each. Places of publication for research on Deviant Sects in Islam are dominated by Theosophy, the Journal of Sufism and Islamic Thought. This research is useful so that people are increasingly aware of the emergence of heretical sects in Islam.